Johnson and the Internet - Crystal, David (Hilda Hulme Lecture Series, 2005)
Professor David Crystal discusses Computer-Mediated Speech (CMC), or Netspeak. In this short book, he presents a discursive timeline of the linguistic quirks of digital interactivity. From framing to flaming, from emoticons to text speak, can we ever communicate effectively in our digital realms? The book is based on a lecture given as part of the Hilda Hulme Memorial Lectures, established in 1985 following a donation from Mr Mohamed Aslam in memory of his wife, Dr Hilda Hulme. The lectures are on the subject of English literature and relate to one of 'the three fields in which Dr Hulme specialised, namely Shakespeare, language in Elizabethan drama, and the nineteenth-century novel'. This lecture by Professor David Crystal was originally published by the Institute of English Studies, University of London in 2005.